Projeto de intervenção em educação sexual com educadoras e alunos de uma pré-escola - Maia, Ana Cláudia Bortolozzi [UNESP]; Pastana, Marcela [UNESP]; Pereira, Patricia Cristine [UNESP]; Spaziani, Raquel Baptista [UNESP] (My University, 2011)
Childhood sexuality is a polemic theme among pre-school educators. This text describes an extension project that aimed to observe the manifestation of children’s sexuality in a pre-school and to intervene by offering a space for dialogue, reflection and better understanding about childhood sexuality. The participants were seven teachers and whole group of children from a selected pre-school. It was observed (1) among the educators: the different games applied according to gender; how tolerant the teachers were regarding to boys bad behavior; vigilance against the homosexuality and constant motivation to female vanity and beauty. (2) Among the children: sexist stereotypes; manifestations of racism and prejudice; curiosity and interest about the body and sexuality and the use of insulting words concerning body beauty. The teacher education discussed theoretical and practical issues about the development of the sexuality in the childhood and the sexual education of their students. The project observed that a sexual education project can be put into practice in a pedagogical and ethical way in a pre-school environment.

A sexualidade infantil é um tema polêmico entre educadores de pré-escolas. Este texto descreve um projeto de extensão que observou a manifestação da sexualidade de crianças em uma pré-escola e interveio oferecendo um espaço de diálogo, reflexão e esclarecimento sobre sexualidade na infância. Participaram do trabalho sete educadoras e as crianças da pré-escola. Observou-se entre: (1) Educadoras: propostas de brincadeiras diferenciadas pelo gênero, a indisciplina tolerada nos meninos, vigília contra a homossexualidade, incentivo constante da vaidade e da estética feminina. (2) Crianças: estereótipos sexistas, manifestações de racismo e preconceito, curiosidade e interesse sobre o corpo e sexualidade, uso de palavrões, preocupações com a estética do próprio corpo. A formação com as professoras discutiu questões teóricas e práticas sobre o desenvolvimento da sexualidade na infância e a educação sexual de seus alunos. O projeto evidenciou que o trabalho de educação sexual pode ser realizado de modo pedagógico e ético na pré-escola.
Intervention project in sexual education with pre-school educators and students
Keywords: Childhood sexuality; Sexual education; Teacher education; Sexualidade infantil; Educação Sexual; Formação de professores